2019
DOI: 10.22392/actaquatr.484963
|View full text |Cite
|
Sign up to set email alerts
|

Kadıköy Barajı’nın (Edirne/Türkiye) Planktonik Microcrustacea (Copepoda, Cladocera) Faunasi ve Mevsimsel Değişimi

Abstract: This study was carried out to determine the diversity, abundance and seasonal distribution of microcrustacea (Cladocera, Copepoda) in Kadıköy Reservoir. For this purpose, microcrustacea and water samples were taken at monthly intervals from March 2010 to February 2011 in three different stations from the reservoir. As a result of qualitative and quantitative analyses of the samples, a total of 27 taxa, 19 taxa from Cladocera and 8 taxa from Copepoda were identified. The quantitative evaluation of the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…No such a long term and more detailed study have been carried out in the dam lakes in the Thrace region where the Kayalıköy dam is located. However, along with planktonic organisms in Süloğlu and Kadıköy dam lakes, some physicochemical properties of water have also been studied (Güher and Çolak 2015;Tokatlı et al 2017;Güher 2019). As a result of these studies, it was reported that the water of Süloğlu reservoir is in Class I and II and of oligo-mesotrofic character in most parameters, and that of Kadıköy reservoir is in Class II and of meso-eutrophic character.…”
Section: Leadmentioning
confidence: 99%
“…No such a long term and more detailed study have been carried out in the dam lakes in the Thrace region where the Kayalıköy dam is located. However, along with planktonic organisms in Süloğlu and Kadıköy dam lakes, some physicochemical properties of water have also been studied (Güher and Çolak 2015;Tokatlı et al 2017;Güher 2019). As a result of these studies, it was reported that the water of Süloğlu reservoir is in Class I and II and of oligo-mesotrofic character in most parameters, and that of Kadıköy reservoir is in Class II and of meso-eutrophic character.…”
Section: Leadmentioning
confidence: 99%